(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Chlorhexidine is well known to be an effective antiseptic in managing wound care and oral diseases. Currently, there are a limited number of chlorhexidine formulations available, with the majority being conventional mouth rinses, gels, pocket chips and varnishes, and the minority being oral disintegrating films. Therefore, this study aims to formulate and evaluate oral fast-dissolving films of chlorhexidine with an additional objective to improve patient compliance and convenience while maintaining its efficacy as its standard oral rinses. Six formulations of chlorhexidine oral fast-dissolving films were prepared by solvent casting method. The films were then evaluated for their weight, dimensions, thickness, folding endurance, moisture content, in vitro disintegration time, surface pH, antimicrobial activity, and stability studies. Fourier-Transform Infrared spectroscopy (FTIR) of the films was also analysed. The films showed acceptable physicochemical and stability properties with a weight range of 33.23 to 85.90 mg, a thickness range of 0.32 to 0.79 mm, a folding endurance range of 21 to 437, a moisture content range of 9.16 to 26.22%, a disintegration time range of 4.91 to 7.09 mins and a surface pH range of 7.24 to 8.12. FTIR spectra displayed the incorporation of the film composition without any interactions. The antimicrobial activity of the chlorhexidine films was unable to produce satisfactory results despite using a potent antiseptic. It was concluded that despite not having fast-dissolving properties, the chlorhexidine films were still able to provide promising results that can be of great importance in managing oral diseases such as caries and gingival inflammation.